Meaningful Care
XVI, 190 p.
Keywords: It is crucial for the quality of care of people with mental retardation that care providers experience their work as meaningful. A complexity, however, is the fact that this care is divided amongst a range of professions. This book addresses issues of meaning (meaning of care and meaning of life) from all the different professional perspectives involved. Such a multidisciplinary approach is unique and has never before been followed. The book contains the results of a series of interviews in which parents of people with mental retardation were asked what they conceive to be meaningful care. The results are placed in relation to experiences and conceptions of professional caregivers. Moreover, the study analyzes the cultural, philosophical, and theological significance of the concept, `meaningful care'. Finally, the book explores the relevance of this concept for practical professions such as medical care, social work, educational psychology, pedagogic counseling, and pastoral care. Scholarly depth is combined with experiential knowledge of professional practice. Hence, this book is an outstanding source of reflection for all those who work professionally with people with mental retardation.